Clinical and Environmental Isolates of Cryptococcus gattii from Australia That Retain Sexual Fecundity - Campbell, Leona T. (American Society for Microbiology, 2005)
Cryptococcus gattii is a primary pathogenic yeast that causes disease in both animals and humans. It is closely related to Cryptococcus neoformans and diverged from a common ancestor ∼40 million years ago. While C. gattii has a characterized sexual cycle dependent upon a dimorphic region of the genome known as the MAT locus, mating has rarely been observed in this species. In this study, we identify for the first time clinical (both human and veterinary) and environmental isolates from Australia that retain sexual fecundity. A collection of 120 isolates from a variety of geographic locations was analyzed for molecular type, mating type, and the ability to develop mating structures when cocultured with fertile tester strains. Nine isolates produced dikaryotic filaments with paired nuclei, fused clamp connections, and basidiospores. DNA sequence analysis of three genes (URA5, the MATα-specific SXI1α gene, and the MATa-specific SXI2a gene) revealed little or no variability in URA5 and SXI2a, respectively. However across the 108 MATα strains sequenced, the SXI1α gene was found to exist as 11 different alleles. Phylogenetic analysis found most variation to occur in the more fertile genotypes. Although some lineages of Australian C. gattii have retained the ability to mate, the majority of isolates were sterile, suggesting that asexuality is the dominant mode of propagation in these populations.